2017
DOI: 10.15628/holos.2017.6374
|View full text |Cite
|
Sign up to set email alerts
|

Use of Linear Alkylbenzene Sulfonate (Las) and Polycarboxylate-Ether (Pce) as Reagents in Iron Ore Flotation

Abstract: Flotation is one of the separation techniques that has been used by the mineral industry and its importance has increased due to its better performance in the concentration of low grade ores. Specific chemical reagents are used in flotation in order to promote the hydrophobicity control of minerals dispersed in a pulp, among them, surfactants have been studied with good results. In this study, a substance based on Linear Alkylbenzene Solfonate (LAS), and a concrete admixture based on Policarboxilate--ether (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Sodium thiocyanate can improve the early rate of the hydration reaction in Portland cement [28]. Alkylbenzene sulfonate is the bio-degradable surfactant normally used in cleansing products and the air-entraining agent for cement-based composite materials [29,30]. Although hydrochloric acid can attack cement-based materials by reacting with calcium hydroxide [31][32][33], it was found that hydrochloric acid could be used to improve the pozzolanic reactivity of the waste such as agricultural waste [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium thiocyanate can improve the early rate of the hydration reaction in Portland cement [28]. Alkylbenzene sulfonate is the bio-degradable surfactant normally used in cleansing products and the air-entraining agent for cement-based composite materials [29,30]. Although hydrochloric acid can attack cement-based materials by reacting with calcium hydroxide [31][32][33], it was found that hydrochloric acid could be used to improve the pozzolanic reactivity of the waste such as agricultural waste [34].…”
Section: Methodsmentioning
confidence: 99%
“…The LS enhances the freeze-thaw resistance by forming micro and mesopores which prevent the freezing of water within these pores due to the limited space [27]. The ABS is an air-entraining agent for the forming of microscopic pores that can improve the freeze-thaw resistance of cement-based composite materials [30]. In addition, according to Wise et al [28], besides being an accelerator for the hydration reaction at low temperatures, the addition of NaSCN into the cement-based material could prevent the freezing of water within the microstructure as well.…”
Section: Freeze-thaw Resistance Of Fc Samplesmentioning
confidence: 99%